2010
DOI: 10.1097/spv.0b013e3181ee6847
|View full text |Cite
|
Sign up to set email alerts
|

Vaginal Hysterectomy at the Time of Transvaginal Mesh Placement

Abstract: : When incisions for mesh placement are kept separate from the vaginal cuff, transvaginal mesh reconstruction can be safely performed at the time of hysterectomy.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

0
1
0

Year Published

2011
2011
2015
2015

Publication Types

Select...
2

Relationship

1
1

Authors

Journals

citations
Cited by 2 publications
(1 citation statement)
references
References 14 publications
0
1
0
Order By: Relevance
“…The odds ratio of a vaginal mesh erosion was no different for those who underwent a hysterectomy at the time of abdominal sacral colpoperineopexy (odds ratio, 0.95; 95% confidence interval, 0.41-2.18; p=.899). Additionally, a recent report by Murphy et al (10) reported on placement of vaginal mesh at the time of vaginal hysterectomy. They retrospectively looked at 40 women with a median follow-up of 12 months and found only a 2.5% erosion rate, which is very comparable to that seen with an ASC.…”
Section: Discussionmentioning
confidence: 99%
“…The odds ratio of a vaginal mesh erosion was no different for those who underwent a hysterectomy at the time of abdominal sacral colpoperineopexy (odds ratio, 0.95; 95% confidence interval, 0.41-2.18; p=.899). Additionally, a recent report by Murphy et al (10) reported on placement of vaginal mesh at the time of vaginal hysterectomy. They retrospectively looked at 40 women with a median follow-up of 12 months and found only a 2.5% erosion rate, which is very comparable to that seen with an ASC.…”
Section: Discussionmentioning
confidence: 99%